Osoby niepełnosprawne w sytuacji podwójnego wykluczenia w wybranych krajach Afryki Południowej - Belzyt, Joanna Iza (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
In South African countries education plays the important role in the context of double exclusion occurance of people with disabilities living in those areas. Factors like race, gender, social origin or disability affect social inequalities which powerful strength in society is strictly connected with a dominant ideology or state policy (eg. apartheid in South Africa). People with disabilities undergoing social exclusion caused by their social origin as African natives, simultaneously undergo exclusion caused by disability. In this context, apart from (the exclusion rooted in) the “heritage” of apartheid, one can also find a very meaningful factor folk beliefs, healers and shamans. Hence, disability, according to the particular area of the country and local folk beliefs, is perceived and understood as punishment or a thrown charm which eventually makes families being ashamed of their disabled children or relatives, force them to hide them for fear of ostracism, violence, ritual mutilation or death.